The Role of Fusion Technique of Computed Tomography and Non-echo-planar Diffusion-weighted Imaging in the Evaluation of Surgical Cholesteatoma Localization - Ayse Ozlem BALIK; Lutfu SENELDIR; Aysegul VERIM; Sema ZER TOROS (Medeniyet Medical Journal)
Objective: In recent years, the fusion of computed tomography (CT) and non-echo-planar diffusion-weighted magnetic resonance imaging (non-EPI DWI) has been preferred in cholesteatoma localizations. This study aimed to investigate the role of CT and non-EPI DWI fusion imaging in cholesteatoma localizations. Methods: This retrospective study included 39 patients who underwent chronic otitis media operation [mean age of 35.10+-15.33 years (18-67 years), 64.1% female, and 35.9% male] and had preoperative high-resolution temporal bone CT and non-EPI DWI examinations. Images were sent to the Advantage Workstation VolumeShare 7 for fusion. These selected images were fused on the workstation and were manually corrected by the radiologist. The sensitivity, specificity, positive and negative predictive values, and diagnostic accuracies of fused images of CT and non-EPI DWI were evaluated according to anatomic cholesteatoma localizations based on surgical data. Results: The sensitivity, specificity, positive and negative predictive values, and diagnostic accuracies of non-EPI DWI for detecting cholesteatomas were 97.14%, 75.00%, 97.14%, 75.00%, and 94.87%, respectively. Three true-negative, one false-positive, and one false-negative case were observed according to surgical results in detecting the presence of a cholesteatoma with non-EPI DWI. Moderate agreement was determined between the surgical and radiological results in detecting the presence of a cholesteatoma (k=0.721). Detecting the lesion of localization on the fused images compared to surgical found an almost perfect agreement in the mastoid antrum (k=0.948), strong agreement in the hypotympanum and mastoid cells (k=0.894), moderate agreement in the epitympanum (k=0.653), and weak agreement in those in the mesotympanum (k=0.540). Conclusions: The surgeons' determinations are supported by the guidance of temporal CT and non-EPI DWI fused images. Therefore, preferring the fusion imaging technique could increase the quality of life by reducing unnecessary operations.